Role of tumor necrosis factor in macrophage leishmanicidal activity in vitro and resistance to cutaneous leishmaniasis in vivo. - Theodos, C M (1991)
Recombinant human tumor necrosis factor (TNF) and purified murine TNF were both able to activate macrophages to destroy intracellular Leishmania major in vitro. In addition, parasitizing macrophages with L. major markedly increased the ability of the cells to produce TNF. Finally, when mice were vaccinated with an avirulent form of L. major, the animals produced large amounts of TNF but no gamma interferon in response to infection with virulent L. major. Treating these mice with a neutralizing anti-TNF antibody led to partial but not complete inhibition of the resistant state, which suggests that factors other than TNF and gamma interferon contribute to resistance to L. major.